Mapping research trends from 35 years of publications in Distance Education. Issue 3 (1st September 2016) - Zawacki-Richter, Olaf; Naidu, Som
Abstract: This article maps out trends in distance education research and scholarship from 35 years of publications in the Distance Education journal. Titles and abstracts of 515 full papers were analyzed using the text-mining tool Leximancer TM to identify and describe themes in distance education research covered by these publications in the journal over the period 1980–2014. Analysis of titles and abstracts over 5-year periods reveals the following broad emerging themes over the seven time periods: professionalization and institutional consolidation (1980–1984), instructional design and educational technology (1985–1989), quality assurance in distance education (1990–1994), student support and early stages of online learning (1995–1999), the emergence of the virtual university (2000–2004), collaborative learning and online interaction patterns (2005–2009), and interactive learning, MOOCs and OERs (2010–2014). The place of these themes within waves of alternating institutional and individual research is discussed.